Gut metabolomic profiles in paediatric ulcerative colitis patients prior to and after receiving faecal microbiota transplants - Khalessi Hosseini, Parastou S.; Wang, Beibei; Luan, Yihui; Sun, Fengzhu; Michail, Sonia (Gut microbiome (Cambridge, England), 2023)
Ulcerative colitis (UC) is an immune-mediated inflammation of the colonic mucosa. Gut microbiota dysbiosis may play a significant role in disease pathogenesis by causing shifts in metabolomic profiles within the gut. To identify differences and trends in the metabolomic profile of paediatric UC patients pre- and post-faecal microbiota transplants (FMT). Forty-six paediatric patients with mild-to-moderate UC and 30 healthy paediatric patients were enrolled in this study. Baseline stool samples were collected prior to FMT initiation and at months 1, 3, 6, and 12 post-FMT. Pediatric Ulcerative Colitis Activity Index (PUCAI) scores were calculated at baseline and months 1, 3, 6, and 12 after FMT. The average Bray–Curtis dissimilarities to healthy subjects decreased after FMT. In principal coordinate analysis plots, UC patients’ centroids drew nearer to healthy individuals. The variance explained by phenotype (Healthy versus UC) reduced and remained significant. From 1 to 3 months after FMT, PUCAI trends were statistically significant and decreasing. PUCAI scores remain flat starting 6 months after FMT. This study concludes that paediatric UC patients have a significantly different baseline metabolite profile than healthy controls. Although being time limited, FMT significantly altered these metabolite profiles and shifted them towards that of healthy controls.